Micralestes (Characiformes, Alestidae) of the lower Congo River, with a description of a new species endemic to the lower Congo River rapids in the Democratic Republic of Congo - Stiassny, Melanie L.j.; Mamonekene, Victor (Zootaxa, 2007)
A new dwarf alestid from the vicinity of Inga on the lower Congo River, Bas Congo Province, Democratic Republic of Congo is described. Assignment of the new taxon to the poorly defined genus, Micralestes, is discussed and justified on the basis of available morphological character data. With the recognition of Micralestes schelly sp. nov., a total of six Micralestes are now known to inhabit the 350 km stretch of the Congo River from Pool Malebo to Boma near the river’s estuary. These are Micralestes acutidens (Peters, 1852), Micralestes humilis Boulenger, 1899, Micralestes lualabae Poll, 1967, Micralestes holargyreus (Günther, 1873), Micralestes stormsi Boulenger, 1902, and the new species Micralestes schelly. Of these Micralestes schelly and Micralestes holargyreus are considered herein as restricted-range endemics of the lower Congo River. An illustrated key to Micralestes of the lower Congo River is provided.